Perceptions of medical students about Pathology training - Shubha P Bhat; Lakshmi Cheriyanath; Malavika Nair; Mahendran M Nair (Journal of Pathology of Nepal)
Background: An understanding of pathology is the foundation for good clinical practice. Pathology is a vast subject with limited teaching hours. Understanding the students' perspectives is essential for making new roadmaps for teaching.